Pengaruh Waktu Penahanan pada Perlakuan Panas Paska Pengelasan terhadap Ketangguhan Sambungan Las Baja - Muhamad Fitri; Bambang Sukiyono; Martua Limido Simanjuntak (University of Muhammadiyah Jakarta, 2019)
One of the welding methods that is widely used today because it is easier to operate, more practical in its use, can be used for all welding positions and more efficient is called Shield Metal Arc Welding (SMAW). In this welding, the base metal and filler metal will experience thermal cycles which lead to local heating and cooling processes resulting in residual stress and distortion in the material. This residual stress must be removed because it causes a decrease in the mechanical properties of the material. The most widely used method is the thermal method that is by Post Weld Heat Treatment (PWHT). The success of The post-weld heat treatment in removing residual stresses in PWHT is influenced by the holding time. This study aims to examine the effect of holding time on heat treatment, on the weld toughness of steel. In this study, the type of welding used was SMAW welding, the material used was steel AISI 4130, the electrodes used were LB-7018-1 standard application and AWS classification A5.1 E7018-1. The test holding temperature is 650oC. The holding time of testing uses three variables, namely: 2.5 hours, 4.5 hours, 6.5 hours. The Impact testing is done by the Charpy method. From this study, the influence of holding time variation on PWHT holding temperature on the weld strength of AISI 4130 steel was obtained.